COMPARISON OF EFFECTIVENESS OF A PROGRESSIVE MOBILIZATION AND MOZART MUSIC THERAPY ON NON-INVASIVE HEMODYNAMIC STATUS CHANGES IN PATIENTS WITH HEAD INJURY IN THE INTENSIVE CARE UNIT - Novi Indriani; Bedjo Santoso; Arwani Arwani; Mardiyono Mardiyono (Belitung Raya Foundation, Indonesia, 2018)
Background: The instability of hemodynamic status in patients with head injury with decreased consciousness has an effect on the increase of intracranial pressure. The recovery of hemodynamic status can be done through nursing intervention either by providing a sensory stimulus (music therapy) or motor stimulus (progressive mobilization). Objective: To compare the effectiveness of progressive mobilization of level I with Mozart's music therapy on non-invasive hemodynamic status changes in patients with head injury with decreased awareness. Methods: This was a quasi-experimental study with pretest-posttest design. There were 34 samples selected using consecutive sampling, which 17 samples assigned in a group of progressive mobilization and group of music therapy. Paired t-test and Wilcoxon test were used for paired group, and Independent t-test and Mann-Whitney test for unpaired group. Results: Progressive mobilization of level I had significant effect on changes in systolic blood pressure (p = 0.0001), diastolic blood pressure (p = 0.002) and MAP (p = 0.019), and no significant effect on heart rate (p = 0.155), respiration (p = 0.895) and oxygen saturation (p = 0.248). Mozart's music therapy had a significant effect on changes in systolic blood pressure (p = 0.0001), diastolic blood pressure (p = 0.0001), respiration (p= 0.032) and oxygen saturation (p = 0.008), but no effect on MAP (p = 0.561). There was a significant difference between the two interventions in the systolic blood pressure and heart rate variables (p <0.05), while the diastolic blood pressure, MAP, respiration and oxygen saturation variables did not show a difference (p> 0.05). Conclusion: The Mozart's music therapy is more effective on non-invasive hemodynamic status changes in patients with head injury with decreased consciousness compared with progressive mobilization of level I.